Isolation and recovery of extracellular vesicles using optically-induced dielectrophoresis on an integrated microfluidic platform - Chen, Yi-Sin; Lai, Charles Pin-Kuang; Chen, Chihchen; Lee, Gwo-Bin (Lab on a chip, 2021)
Cell-released, membrane-encapsulated extracellular vesicles (EVs) serve as a means of intercellular communication by delivering bioactive cargos including proteins, nucleic acids and lipids. EVs have been widely used for a variety of biomedical applications such as biomarkers for disease diagnosis and drug delivery vehicles for therapy. Herein, this study reports a novel method for label-free, contact-free isolation and recovery of EVs via optically-induced dielectrophoresis (ODEP) on a pneumatically-driven microfluidic platform with minimal human intervention. At an optimal driving frequency of 20 kHz and a voltage of 20 Vpp, an ODEP force from a 75 μm moving light beam was characterized to be 23.5-97.7 fN in 0.2 M sucrose solution. Furthermore, rapid enrichment of EVs with a small volume of only 27 pL in 32 s achieved an increase of 272-fold by dynamically shrinking circular light patterns. Moreover, EVs could be automatically isolated and recovered within 25 min, while achieving a releasing efficiency of 99.8% and a recovery rate of 52.2% by using an integrated microfluidics-based optically-induced EV isolation (OIEV) platform. Given the capacity of label-free, contact-free EV isolation, and automatic, easy-releasing EV recovery, this integrated OIEV platform provides a unique approach for EV-based disease diagnosis and drug delivery applications. A novel method for automating label-free, contact-free isolation and recovery of EVs by using ODEP on a microfluidic platform was developed and achieved effective EV enrichment (272-fold locally increase), releasing (99.8%) and recovery (52.2%).